Outcomes in unilateral primary aldosteronism after surgical or medical therapy. (26th October 2020) - Puar, Troy H.; Loh, Lih M.; Loh, Wann J.; Lim, Dawn S. T.; Zhang, Meifen; Tan, Pei T.; Lee, Lynette; Swee, Du S.; Khoo, Joan; Tay, Donovan; Tan, Sarah Y.; Zhu, Ling; et al.
Abstract: Context: Studies find surgery superior to medications in the treatment of primary aldosteronism (PA). It would be ideal to compare surgical and medical therapy in patients with unilateral PA only, who have the option between these treatment modalities. However, this is challenging as most patients with unilateral PA on adrenal vein sampling (AVS) undergo surgery. Objective: To compare outcomes of surgery and medications in patients with confirmed or likely unilateral PA. Design: Retrospective cohort study of 274 patients with PA managed at two referral centres from 2000 to 2019. Patients: 154 patients identified with unilateral PA using AVS and a validated clinical prediction model were treated with surgical ( n  = 86) or medical ( n  = 68) therapy. Measurements: Primary outcome was a composite incident cardiovascular event comprising acute myocardial infarction, coronary revascularization, stroke, atrial fibrillation or congestive cardiac failure. Secondary outcomes were clinical and biochemical control. Results: Cardiovascular outcomes were comparable, with the surgery group having an adjusted hazard ratio of 0.93 (95% CI: 0.32–2.67), p  = .89. Both treatments improved clinical and biochemical control, but surgery resulted in better systolic blood pressure, 133.0 ± 11.7 mmHg versus 137.9 ± 14.6 mmHg, p  = .02, and lower defined daily dosages of antihypertensive medications, 1.0 (IQR 0.0–2.0) versus 2.6 (IQR 0.8–4.3), p  < .001. In addition, 12 of 86 patients in the surgery group failed medical therapy before opting for surgery. Conclusion: In patients with unilateral PA who can tolerate medications, medical therapy improves clinical and biochemical control, and may offer similar cardiovascular protection. However, surgery reduces pill burden, may cure hypertension and is recommended for unilateral PA.